Standardy corporate governance powszechnych towarzystw emerytalnych - spojrzenie na zasady i kontrowersje - Czerwińska, Teresa Tatiana (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The requirement to promote good corporate governance in Pension Societies is receiving increased international attention. Pension Societies must be prudently managed. Corporate governance of Pension Societies must refer to the rules and procedures put in place within a corporation for the management and control of its business and affairs. Individual Pension Societies will adopt different approaches to corporate governance, taking into account the scope, complexity, and risk profile of its organization. The paper presents the analysis of corporate governance standards of Pension Societies in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 73-81